Integrating 3D-printed customized guides with hemicorticotomy bone transport: clinical outcomes in chronic osteomyelitis management - Yimurang Hamiti; Patiman Abudureyimu; Gang Lyu; Jianwu Zhang; Xin Xu; Aihemaitijiang Yusufu; Maimaiaili Yushan (BMC Musculoskeletal Disorders)
Abstract Purpose Chronic osteomyelitis with large bone defects remains a challenging condition in orthopedic surgery. This study aimed to evaluate the clinical efficacy of hemicorticotomy bone transport assisted by 3D-printed customized guides in the treatment of chronic osteomyelitis with bone defects. Methods A retrospective analysis was conducted on 21 patients with chronic osteomyelitis treated with hemicorticotomy bone transport with 3D-printed guide assistance between January 2015 and January 2021. Preoperative planning utilized 3D CT reconstruction for precise guide design and osteotomy placement. The surgical technique involved hemicorticotomy, placement of the 3D-printed guide, and gradual bone transport using a monolateral external fixator. Clinical outcomes were assessed using the Association for the Study and Application of Methods of Ilizarov (ASAMI) scoring system. The external fixation time (EFT), external fixation index (EFI), and complications evaluated using the Paley classification were recorded. Results The mean bone defect size was 7.9 ± 2.0 cm. The average follow-up period was 28.6 ± 6.4 months. The mean external fixation time was 289.4 ± 52.7 days, with an external fixation index of 36.8 ± 4.2 days/cm. According to the ASAMI criteria, the bone results were excellent in 17 patients (81%), good in 3 (14%), and fair in 1 (5%). The functional results were excellent in 15 patients (71%), good in 4 (19%), and fair in 2 (10%). Complete eradication of the infection and union at the docking site were achieved in all patients. The complication rate was 38% and all of which were successfully managed. Conclusion Hemicorticotomy bone transport assisted by 3D-printed customized guides is an effective treatment for chronic osteomyelitis with bone defects. This technique offers excellent bone healing, favorable functional results, and a relatively low complication rate. Further studies with larger sample sizes are warranted to validate these findings.